Improving the content of building material courses through sustainability - Kasapoğlu, Esin (WIT PRESS, ASHURST LODGE, SOUTHAMPTON SO40 7AA, ASHURST, ENGLAND, 2008)
Wasting the resources of the world is one of the most important problems facing humanity at the end of the 20(th) century. In 1992 the UNO World Conference on Environment and Development held in Rio de Janeiro and the issues of sustainable development were studied thoroughly in all branches of science and technology. The architecture and construction industry has also inevitably followed this, as the building industry is a major consumer of materials and energy. The production of building materials and the use of pollutant substances are the source of pollution. As environmental labelling has an increasing popularity, today it is possible to produce building materials and raw materials through an ecological perspective. Sustainability can be defined as living in such a way to meet the needs of the present without comprising the ability of future generations to meet the needs of the future. Sustainability is both a social and environmental concept. As it considers the needs of the unborn, it is a social concept and as it addresses the effect of pollution and resource management on the ecological system of earth, it is an environmental concept. As it seeks to quantify the tolerable limits for consumption such that we can live instead of depleting the principle resources of earth, it is also an economic concept. Today it is important for an architect to be aware of sustainability. An architect should gain consciousness of sustainability during education. Although having necessary courses in the curriculum is important, reviewing existing courses through the view of sustainability is more important. In this paper a proposal of content for building material courses will be prepared. The content of building material courses will be reviewed through the view of sustainability and a new content will be presented.
Keywords: building materials; sustainability; ecology; environment; education; yapı malzemeleri; sürdürülebilirlik; ekoloji; çevre; eğitim